ANALISIS PERMASALAHAN DAN PENYELESAIAN PADA PELAYANAN SERTIFIKASI HALAL DI KABUPATEN SUMBAWA - Sucihati, Roos Nana; Heriwibowo, Dedy; Kusmayadi, Andi (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to determine the problems and solutions to halal certification services in Sumbawa Regency. This study uses a quantitative descriptive approach. The type of data used in this study is quantitative data obtained directly from primary sources using a research instrument in the form of a questionnaire. The population in this study were all business actors who were accompanied and facilitated by halal certificates in Sumbawa Regency, totaling 723 business actors. Seeing that the number of business actors who have been assisted and facilitated with halal certificates in Sumbawa Regency is relatively large, so it is not possible for researchers to study all the elements in the population, the researchers chose 20% of the total population as representatives to be the sample so that the number of respondents in this study was 145 people. Based on the results of the data analysis that has been carried out, it can be concluded that the Halal Center of Sumbawa Regency has served halal certificate applicants well, although there are several aspects that still require improvement. In each service element, there are problems faced in implementing the halal certification program in Sumbawa Regency. However, the Halal Center of Sumbawa Regency focuses its attention on efforts to provide the best possible service to the community so that it can provide the right solution to overcome these problems. This aims to foster a sense of trust and satisfaction in the community as service users.